Exopolysaccharide from mycelium of Ganoderma lucidum as a potential additive for juvenile red hybrid tilapia (Oreochromis sp.) / Janathu Ferdaus Pajaru Rahman - Janathu Ferdaus , Pajaru Rahman (2020)
Functional feed additives are added during feed preparation to improve the growth performance and cellular defense for the fishes. Interaction of cellular biomolecules and dysfunction of red hybrid tilapia (Oreochromis sp.) could be avoided by strengthening the antioxidant defense with antioxidant rich sources. As for this, a bioactive polysaccharide of Ganoderma lucidum was found to have its antioxidant bioactivities. Thus the potential of exopolysaccharide (EPS) extracted from the mycelium of G.lucidum as feed additive for red hybrid tilapia was evaluated in this research. In this experiment, one hundred twenty (120) juveniles were randomly divided into four groups and designated with experimental diets of EPS at 1.0 g/kg, 2.0 g/kg, 3.0 g/kg and control group with 0 g/kg of EPS. Growth performance was assessed in the term of weight gain (WG), specific growth rate (SGR), feed conversion ratio (FCR), feed intake (FI) and survival rate (SR). Antioxidant activity of Glutathione S-transferase (GST) and Catalase (CAT) were determined from liver samples collection of red hybrid tilapia. Fatty acid profile was expressed as fatty acid methyl esters (FAME). The results of the present study indicate that the growth performance on WG, SGR, FCR, FI, and SR of red hybrid tilapia were positively impacted by the different inclusion of EPS from mycelium G. lucidum. GST activity decreased in red hybrid tilapia fed with 1g/kg and 2g/kg of EPS as feed additive. In contrast, CAT activity was lower in the control group, which might attribute due to the presence of beta glucan in EPS feed. Experimental diet of 1 g/kg and 2 g/kg of EPS shows conceivable fatty acid content in red hybrid tilapia. In conclusion, EPS from the mycelium of G.lucidum can be taken as feed additive on red hybrid tilapia without enforcing any negative impact on the growth performance, antioxidant activity and fatty acid profile. Briefly, the present study indicated 2g/kg sufficiently acceptable as a feed additive as it shows improved growth performance as well as exhibit an antioxidant effect with an improved fatty acid profile of the red hybrid tilapia.